CONCENTRAÇÃO REGIONAL DA INDÚSTRIA DA CERÂMICA VERMELHA NA PARAÍBA, BRASIL (2006 – 2020) - Graziela Pinto de Freitas; Edvaldo Pereira Santos Júnior; Amadeu Junior da Silva Fonseca; Clarisse Freire Barboza Maurício; Luiz Moreira Coelho Junior (Gestão & Regionalidade)
This work analyzed the regional concentration of the red ceramic sector, from 2006 to 2020. It carried out a statewide analysis of the sector's conjuncture, its relation to firewood consumption and the regional concentration was determined through the indicators: Concentration Ratio CR(k ), Herfindahl-Hirschman Index (HHI), Theil entropy (E) and the Gini coefficient (G). The results showed that Borborema has the highest number of red ceramic companies when compared to the other mesoregions of the state. The CR(k) rated with moderately low concentration. The HHI for municipalities and microregions showed low concentration. The municipal, micro-regional and meso-regional E indices of Paraíba indicated deconcentration. G showed weak to average inequality for municipalities and microregions and weak inequality for mesoregions. Thus, it was concluded that the ceramic sector in Paraíba is not concentrated and that the supply is associated with raw material stocks and the energy vector of firewood.